2002
DOI: 10.1046/j.1468-2982.2002.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate: A Case Series Study in Migraine Prophylaxis

Abstract: We reviewed the electronic records of 74 migraine patients treated with topiramate for more than 6 weeks. Twenty-four patients had episodic migraine and 50 had chronic (transformed) migraine. Most (81%) started treatment at 25 mg per day and reached a dose of 100 mg twice a day (mean dose on the last follow-up visit was 208 mg). The mean headache frequency decreased from 20.6 days to 13.6 days per month (P<0.0001) for all headaches (9.9-5.1 (P<0.0001) and 25.7-17.7 (P<0.001) for episodic migraine and chronic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 13 publications
2
26
0
1
Order By: Relevance
“…The third trial (MIGR-003 study), which compared topiramate to propranolol and placebo, has recently been completed but results are still not available. 18 Young et al evaluated the outcome of 74 migraine patients treated with topiramate in a case series study (73). Twenty four patients had episodic migraine and fifty had chronic migraine.…”
mentioning
confidence: 99%
“…The third trial (MIGR-003 study), which compared topiramate to propranolol and placebo, has recently been completed but results are still not available. 18 Young et al evaluated the outcome of 74 migraine patients treated with topiramate in a case series study (73). Twenty four patients had episodic migraine and fifty had chronic migraine.…”
mentioning
confidence: 99%
“…Topiramate is effective in migraine therapy [Mathew et al, 2002;Young et al, 2002;Silberstein, 2005]. Consistent with this, Goadsby and associate showed that topiramate inhibits neurogenic dural vasodilation by inhibiting CGRP release from prejunctional trigeminal neurons.…”
Section: Treatment Of Migraine Headachesmentioning
confidence: 73%
“…Topiramate has demonstrated efficacy for the treatment of migraine in open-label (Hershey et al, 2002;Mathew et al, 2002;Von Seggern et al, 2002;Young et al, 2002), and double-blind trials (Storey et al, 2001;Brandes et al, 2003;Dodick et al, 2003;Rothrock et al, 2003), significantly decreasing the frequency and severity of migraine, and the need for abortive medications. In a doubleblind trial in 40 patients, topiramate significantly reduced migraine frequency compared with placebo (36% vs 14%) (Storey et al, 2001).…”
Section: Migraine and Pain Syndromesmentioning
confidence: 99%